2016
DOI: 10.3109/10837450.2015.1135343
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo buccal drug delivery of ropinirole hydrochloride in the presence of permeation enhancers: the effect of charge

Abstract: In the current study, the ex vivo permeation of ropinirole hydrochloride (RH) across porcine buccal mucosa in the presence of three permeation enhancers, namely N-trimethyl chitosan (TMC) (positively charged) a chitosan derivative, sulfobutyl ether-β-cyclodextrin (SBE-β-CD) (negatively charged) and hydroxypropyl-β-cyclodextrin (HP-β-CD) (neutral), was investigated. Buccal permeation studies were conducted using Franz diffusion cells. Cumulative amounts of RH were plotted versus time. The presence of the permea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Chitosan has previously been utilised as a release modulator and PE for an array of biological membranes including buccal tissue (Duttagupta, Jadhav et al 2015, Kontogiannidou, Andreadis et al 2017, intestinal tissue (Chougule, Patel et al 2014, Maher, Mrsny et al 2016, Ates, Kaynak et al 2016, nasal cavity (Benediktsdottir, Baldursson et al 2014, Giuliani, Balducci et al 2018. Chitosan has also been scrutinised in the ocular drug delivery due to its permeation enhancement properties; with drugs such as ofloxacin (Di Colo, Burgalassi et al 2004), triamcinolone acetonide (Raval, Khunt et al 2018) and timolol maleate (Rodriguez, Antonio Vazquez et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan has previously been utilised as a release modulator and PE for an array of biological membranes including buccal tissue (Duttagupta, Jadhav et al 2015, Kontogiannidou, Andreadis et al 2017, intestinal tissue (Chougule, Patel et al 2014, Maher, Mrsny et al 2016, Ates, Kaynak et al 2016, nasal cavity (Benediktsdottir, Baldursson et al 2014, Giuliani, Balducci et al 2018. Chitosan has also been scrutinised in the ocular drug delivery due to its permeation enhancement properties; with drugs such as ofloxacin (Di Colo, Burgalassi et al 2004), triamcinolone acetonide (Raval, Khunt et al 2018) and timolol maleate (Rodriguez, Antonio Vazquez et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…When triclosan complexed with SBECD or HPBCD (2-hydroxypropyl-beta-cyclodextrin, a neutral CD derivative) no difference was found in adhesion to porcine buccal adhesion ( Sigurdsson et al, 2002 ). In a similar study, the authors found only a slightly higher transport of SBECD/roprinolone compared to HPBCD/roprinolone across porcine buccal epithelium: 28 and 24% improvement compared to buffer only ( Kontogiannidou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 85%
“…Detachment of the epithelium from underlying stroma and mild disorganization at basal membrane are illustrated in the micrographs of Figure 7c and Figure 8c for Me-β-CD, with only rare acantholysis and inter-epithelial gaps in tablet form. In Figure 7d and Figure 8d, desquamation of superficial keratinocytes and mild disorganization of collagen beneath basal membrane could be identified for HP-β-CD [3,8,29]. The loss of the superficial cell layers might imply interactions between the CDs and the epithelial lipids given that CDs can induce lipid solubilization [30].…”
Section: Resultsmentioning
confidence: 99%
“…Buccal mucosa is an alternative site for the delivery of drugs into the systemic circulation [1]. The drug administered through the buccal mucosa enters to the systemic circulation directly via the jugular vein [2], minimizing the first-pass hepatic metabolism, and avoiding the adverse gastro-intestinal tract [3]. Buccal delivery of active pharmaceutical ingredients (APIs) is an alternative, non-invasive route of administration that provides beneficial health effects.…”
Section: Introductionmentioning
confidence: 99%